Fabrication of hydrophobic and magnetic cellulose aerogel with high oil absorption capacity - Chin, S.F.; Ain Nadirah, Romainor; Pang, S.C. (Elsevier B.V, 2014)
Hydrophobic, magnetic and highly porous cellulose aerogel was prepared by a simple method for fast and selective absorption of oil fromwater surface. The aerogel was able to absorb oil up to about 28 times of its own weight within 10 min and could be easily removed and recovered from the water surface by an external magnet. It could be either reused after washing with ethanol, or incinerated with the absorbed oil. The potential application of cellulose aerogel as an oil absorbent was demonstrated by its ease of preparation, low cost of precursor materials, magnetically retrievability, as well as high oil absorption capacity and efficiency.